2020
DOI: 10.1186/s12992-020-00566-3
|View full text |Cite
|
Sign up to set email alerts
|

The north-south policy divide in transnational healthcare: a comparative review of policy research on medical tourism in source and destination countries

Abstract: Medical tourism occupies different spaces within national policy frameworks depending on which side of the transnational paradigm countries belong to, and how they seek to leverage it towards their developmental goals. This article draws attention to this policy divide in transnational healthcare through a comparative bibliometric review of policy research on medical tourism in select source (Canada, United States and United Kingdom) and destination countries (Mexico, India, Thailand, Malaysia and Singapore), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…This is a potential issue, because even if a significant body of research is implicitly policy relevant, failure to make the policy connection is a lost opportunity to frame the public debate and influence policy thinking on medical tourism. For example, while research on medical tourism in Canada has highlighted the ethical, medicolegal and operational challenges arising from Canadian patients traveling abroad to seek medical treatment, it does not adequately address the domestic policy-level drivers that compel them to travel overseas, or gaps in the legal regulation of cross-border healthcare markets that give rise to or exacerbate these challenges [4]. Nonetheless, the quantum of policy-oriented research in the field has been steadily increasing as public policy and the policy sciences have gained greater traction as distinct academic disciplines, and scholars and policymakers have become more interested in understanding how globalization processes, transnational and domestic governance regimes, and government priorities and actions influence the dynamics of international medical travel, and its effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a potential issue, because even if a significant body of research is implicitly policy relevant, failure to make the policy connection is a lost opportunity to frame the public debate and influence policy thinking on medical tourism. For example, while research on medical tourism in Canada has highlighted the ethical, medicolegal and operational challenges arising from Canadian patients traveling abroad to seek medical treatment, it does not adequately address the domestic policy-level drivers that compel them to travel overseas, or gaps in the legal regulation of cross-border healthcare markets that give rise to or exacerbate these challenges [4]. Nonetheless, the quantum of policy-oriented research in the field has been steadily increasing as public policy and the policy sciences have gained greater traction as distinct academic disciplines, and scholars and policymakers have become more interested in understanding how globalization processes, transnational and domestic governance regimes, and government priorities and actions influence the dynamics of international medical travel, and its effects.…”
Section: Discussionmentioning
confidence: 99%
“…A significant amount of research on medical tourism, even if potentially policy-relevant, is undertaken and consumed by researchers outside the formal confines of public policy. As a result, there exists a yawning research-policy gap in the medical tourism field [4]. Such gaps have been observed in both scientific and policy literature on climate change adaptation, which is partly responsible for the disconnect between climate change research and policy [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is likely reflected by the fact that the majority of literature we reviewed did not address the topic from a public health or health system perspective, but instead focused on barriers to development, economic impact, effectiveness of promotional policies, and experiences and satisfaction of medical tourists. This asymmetry in the policy research agenda for South Korea is also reflected in broader published reviews of the medical tourism industry by Virani et al that suggested only a small proportion of medical tourism research focuses on policy issues [56,57]. Crucially, this could create knowledge gaps in how we understand the pros and cons of this industry and further limit the ability to generate evidence-based policymaking in favor of public healthcentered outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews were conducted during 2018 with 33 people who have detailed knowledge of commercial healthcare mediation in and around Delhi (24 respondents) and London (9 respondents), including representatives from 22 facilitation companies. These settings offer a range of specialised healthcare services and are established destinations for domestic and international healthcare users seeking care otherwise unavailable in their home locality [42]. Delhi is a global destination for relatively low-cost medical tourism [19], and attracts users from within and beyond India.…”
Section: Methodsmentioning
confidence: 99%